RESEPSI PEMAHAT DI DESA PRUMPUNG MAGELANG TERHADAP HADIS TENTANG LARANGAN MEMBUAT PATUNG - Ahmad Mustofa (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2019)
Islam, as a doctrine and tradition, has a unique relationship with the world of art, especially the sculpture of art. The uniqueness is born from the meeting of two different entities in the Muslim community, namely (1) religious entities (originating from authoritative texts) which prohibit all forms of likeness to living things and (2) cultural and artistic entities that tend to make living things as perfect objects to become objects of the passion of art. The meeting of the two opposing entities often creates polemics in the community. But in the case of some sculptors in Prumpung Village, the polemic is able to be accommodated in a work of art with objects of living things but still within the corridors and boundaries allowed by the authority of the text. Through the study approach using the theory of reception, this study seeks to explore and understand the model of creative thinking of some sculptors in the village when they have to appreciate their artistic passion in a beautiful work of art without having to confront the sound of authoritative texts.